BLACK SEED (NIGELLA SATIVA) IN ISLAMIC, INDIAN, CHINESE HERITAGE AND MODERN MEDICINE: A BRIEF REVIEW - Ahmed A. Rawwash; Mohamed F.F Bayomy; Amber Mushtaq; Shahira Hassan; Amr Moustafa Yehia Mohammed; Tabish Ishaq Shaikh; Rani Parveen; Ahmed Helmy Saleh; Emad Ahmed Fathy Hussein (International Journal of Islamic and Complementary Medicine, 2025)
Black cumin, or Nigella sativa, is a medicinal plant that is extensively recognised and used on a global scale. This study examines the historical use of black seed in both traditional and modern medicine, as well as its antibacterial, antifungal, antiviral, and anti-parasitic properties. Methods: Data were collected by employing a variety of reputable scientific search engines, such as Google Scholar, ScienceDirect, Taylor & Francis, and Wiley Library…etc. The data was processed and analysed by the author's team to reach the following conclusion: We strongly encourage medical personnel to investigate the integrated application of black cumin as a therapeutic agent alongside contemporary compounds, given the comprehensive antimicrobial efficacy of black seed against pathogenic bacteria, viruses, fungi, and parasites. ABSTRAK Jintan hitam, atau Nigella sativa, merupakan tanaman obat yang dikenal luas dan digunakan dalam skala global. Studi ini meneliti penggunaan jintan hitam secara historis dalam pengobatan tradisional dan modern, serta khasiatnya sebagai antibakteri, antijamur, antivirus, dan antiparasit. Data dikumpulkan dengan menggunakan berbagai mesin pencari ilmiah terkemuka, seperti Google Scholar, ScienceDirect, Taylor & Francis, dan Wiley Library…dll. Data tersebut diproses dan dianalisis oleh tim penulis untuk mencapai kesimpulan berikut: Kami sangat menganjurkan tenaga medis untuk menyelidiki aplikasi terpadu jintan hitam sebagai agen terapeutik bersama senyawa kontemporer, mengingat khasiat antimikroba jintan hitam yang komprehensif terhadap bakteri patogen, virus, jamur, dan parasit.